Religious/spiritual coping and spiritual distress in people with cancer - Gabriela Cruz Noronha Silva; Dáfili Cristina dos Reis; Talita Prado Simão Miranda; Ruan Nilton Rodrigues Melo; Mariana Aparecida Pereira Coutinho; Gabriela dos Santos Paschoal; Érika de Cássia Lopes Chaves (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To investigate the relation between the presence of spiritual distress and use of RSC and sociodemographic, clinical and religious/spiritual variables in people with cancer. Method: Cross-sectional study conducted in an association for support to people with cancer. The data obtained with the tools were analyzed using the Spearman's correlation coefficient and the Mann-Whitney Test. Results: 129 volunteers participated in the study, of which 57% showed moderate spiritual distress, 96% used medium and high positive religious/spiritual coping. Spiritual distress showed positive correlation with negative religious/spiritual coping (P<0.001) and inverse correlation with age (p 0.002). The use of positive religious coping was statistically significant in people who have religious practices (p 0.001). Conclusão: Spiritual distress is a phenomenon that is present in the lives of people with cancer and has significant relation with the use, in a negative manner, of religion/spirituality as a way of coping with the disease.